The effect of earthquake exposure on PTSD symptoms is mediated by intrusive rumination and moderated by gender: a cross-sectional study on the 2023 Kahramanmaraş earthquake survivors - Şenel ÇITAK; İbrahim Dadandı (BMC, 2024)
Abstract Background Evidence suggests that natural disasters, such as earthquakes, can lead to post-traumatic stress disorder (PTSD), with women being particularly vulnerable. However, there is a dearth of knowledge about the underlying mechanisms linking traumatic experiences to PTSD as well as gender differences in the operation of these mechanisms. This study examined the mediating effect of intrusive rumination and the moderating effect of gender on the relationship between earthquake exposure level and PTSD symptoms. Methods This cross-sectional study was conducted 12 months after the devastating earthquake in Kahramanmaraş, Turkey. The sample included 632 adult survivors of the earthquake, including 374 females (59.2%) and 258 males (40.8%). Participants completed a set of questionnaires assessing their demographic information, level of earthquake exposure, intrusive rumination, and PTSD symptoms. Correlation analysis, mediation analysis, and conditional process analysis were employed to evaluate the research hypotheses. Results Findings revealed significant associations between the level of earthquake exposure, intrusive rumination and PTSD symptoms. The level of earthquake exposure significantly predicted PTSD symptoms. Moreover, intrusive rumination partially mediated the relationship between earthquake exposure level and PTSD symptoms. Additionally, the mediating effect of intrusive rumination was more pronounced among females than males. Conclusion This study revealed the significant mediating role of intrusive rumination in the development of post-earthquake PTSD symptoms. By uncovering gender differences in this mechanism, it also emphasized the importance of designing interventions that are sensitive to the varying needs of different demographic groups affected by the disaster in post-disaster mental health interventions.